Preparation and bioactivities of selenium nanoparticles based on a polysaccharide from Dendrobium huoshanense - Pei, Qingyan; Zhang, Leilei; Yang, Yupeng; Gao, Changchang; Ma, Bingji; Xi, Yirong; Wang, Li (Frontiers in Nutrition, 2025)
The present work reported the preparation and characterization of a polysaccharide (DPHs-1) from Dendrobium huoshanense and its influence on bioactivities of selenium nanoparticles (DPH-SeNPs). DPH-SeNPs were synthesized using DPHs-1 as stabilizer and dispersant. Experiments were conducted to investigate the effects of DHPs-1 concentration, temperature, the molar ratio of Vitamin C (Vc) to Sodium selenite (Na2SeO3), and reaction time on the preparation of DHP-SeNPs. Scanning electron microscopy (SEM) revealed that the DHP-SeNPs had a relatively rough and uneven surface. Transmission electron microscopy (TEM) imaging showed DHP-SeNPs were sphere-like in morphology and homogeneously distributed. X-ray diffraction (XRD) analysis indicated that the diffraction peak range changed, leading to the formation of a new substance. The fourier transform infrared spectroscopy (FT-IR) indicated that the main interaction between DHPs-1 and SeNPs occurred in the Se-O bonds, further leading to the stable spherical structure of DHPs-1 decorated SeNPs. Congo red test results revealed that the triple-helix structure of DHP-SeNPs was intact. DHP-SeNPs displayed favorable thermal stability. In vitro antioxidant experiment results showed that DHP-SeNPs had strong scavenging abilities for the 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydroxyl radical, and ABTS+ free radicals and they had good reducing power. The results of Cell Counting Kit-8 (CCK-8) experiments showed that both DHPs-1 and DHP-SeNPs with concentrations in the range of 5–320 μg/mL could promote cell proliferation without cytotoxicity. The results of scratch experiments showed that DHPs-1 and DHP-SeNPs, within concentrations of 20, 40, and 80 μg/mL, significantly promoted scratch healing of macrophage RAW264.7. Bioactivity tests indicated that DHPs-1 and DHP-SeNPs promoted the release of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and interleukin-10 (IL-10) through upregulating the mRNA expression of TNF-α, IL-1, IL-6, and IL-10. In conclusion, DPH-SeNPs have novel bioactivities with promising applications in food and biomedicine.